2020
DOI: 10.1128/jvi.01918-19
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Cloning of a New Western Epstein-Barr Virus Strain That Efficiently Replicates in Primary B Cells

Abstract: The Epstein-Barr virus (EBV) causes human cancers, and epidemiological studies have shown that lytic replication is a risk factor for some of these tumors. This fits with the observation that EBV M81, which was isolated from a Chinese patient with nasopharyngeal carcinoma, induces potent virus production and increases the risk of genetic instability in infected B cells. To find out whether this property extends to viruses found in other parts of the world, we investigated 22 viruses isolated from Western patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…This evidence is complex, though. With the advent of assays for the activity of EBV in cell culture, researchers have screened for cells that release more particles of infectious EBV [ 23 ] and new strains of EBV that could support entry into the lytic phase more efficiently than others [ 24 , 25 , 26 , 27 ]. Multiple studies have subsequently identified sequence variations in the promoter of BZLF1 , an immediate early lytic gene which regulates entry into the lytic phase.…”
Section: Ebv’s Lytic Phase Contributes To Tumorigenesis By Productmentioning
confidence: 99%
“…This evidence is complex, though. With the advent of assays for the activity of EBV in cell culture, researchers have screened for cells that release more particles of infectious EBV [ 23 ] and new strains of EBV that could support entry into the lytic phase more efficiently than others [ 24 , 25 , 26 , 27 ]. Multiple studies have subsequently identified sequence variations in the promoter of BZLF1 , an immediate early lytic gene which regulates entry into the lytic phase.…”
Section: Ebv’s Lytic Phase Contributes To Tumorigenesis By Productmentioning
confidence: 99%
“…While type 1 (B95-8, GD1, and Akata) is the main EBV type prevalent worldwide, type 2 (AG876 and P3HR-1) is as abundant as type 1 in sub-Saharan Africa (13). The EBV variants have different replicative properties and individuals may become superinfected with two or more strains (14)(15)(16).…”
Section: Introduction Epstein-barr Virusmentioning
confidence: 99%
“…From this viewpoint, it is crucial to have a pair of genetically close EBV strains with different biological activities. A new Western-type EBV strain, which is genetically close to the B95-8 strain but has much higher replication efficiency, was recently identified [58]. Likewise, normal versus cancer-derived EBV strains that belong to the same genetic lineage can be subjected to functional comparison.…”
Section: Discussionmentioning
confidence: 99%